A conceptual framework for measuring livelihood resilience: Relocation experience from Aceh, Indonesia. (May 2019) - Sina, Dantje; Chang-Richards, Alice Yan; Wilkinson, Suzanne; Potangaroa, Regan
Highlights: Large-disaster displacement poses livelihood challenges for the relocated people. Self-sufficiency is crucial for livelihood resilience of the relocated individuals. Pairing livelihood interventions with housing recovery is important. Timely needs assessment can offer value in building resilience in livelihoods. Bridging the local and relocated people likely improve the livelihood outcomes of the relocated ones. Abstract: Meeting the global targets of the Sendai Framework for Disaster Risk Reduction and the Millennium Development Goals requires a resilience paradigm to be embedded in the very fabric of community livelihoods. As livelihood holds the key to rapid recovery following a large-scale disaster, building livelihood resilience is a high priority. Through a survey of five post-2004 Indian Ocean tsunami relocated villages in Banda Aceh and Aceh Besar, Indonesia, this research developed a framework for measuring livelihood resilience in cases of post-disaster displacement. The framework suggests that the indicators for measuring resilient livelihood fall into four categories: individual livelihood coping ability, individual wellbeing, access to livelihood resources, and socio-physical robustness of the local community. Relocated individuals seemed to perceive the importance of the first two categories higher than the latter, which implies they think proactive self-sufficiency is more important than other external enabling conditions in building their livelihood resilience. This framework can help government agencies and aid organizations to plan for appropriate livelihood support post-disaster and/or prioritize investment in pre-event livelihood preparedness for individuals, so that they can fare better when facing displacement from a disaster.